Acthar gel treatment suppresses acute exacerbations in a murine model of relapsing-remitting multiple sclerosis. (June 2015) - Cusick, Matthew F.; Libbey, Jane E.; Oh, Luke; Jordan, Shaun; Fujinami, Robert S.
Abstract Acthar gel is indicated for the treatment of acute exacerbations of multiple sclerosis (MS) in adults. Its effects on immune cells during a relapse are unknown. This study investigated the effects of Acthar in an animal model of relapsing-remitting MS, using SJL/J mice sensitized with myelin peptide. All animal studies were reviewed and approved by the University of Utah Institutional Animal Care and Use Committee and conducted in accordance with the guidelines prepared by the Committee on Care and Use of Laboratory Animals, Institute of Laboratory Animals Resources, National Research Council. Mice injected with Acthar to treat the second attack had a significantly lower mean clinical score during relapse and a significantly reduced cumulative disease burden compared to Placebo gel-treated mice. Furthermore, Acthar treatment ameliorated inflammation/demyelination in the spinal cord and markedly suppressed ex vivo myelin peptide-induced CD4+ T cell proliferation.